CB2R agonist prevents nicotine induced lung fibrosis. (9th August 2018) - Wawryk-Gawda, Ewelina; Chłapek, Katarzyna; Zarobkiewicz, Michał K.; Lis-Sochocka, Marta; Chylińska-Wrzos, Patrycja; Boguszewska-Czubara, Anna; Sławiński, Mirosław A.; Franczak, Anna; Jodłowska-Jędrych, Barbara; Biała, Grażyna
Abstract: Introduction : Nicotine stimulates fibroblast proliferation while increasing inflammation and fibrosis of tissues. The cannabinoid receptor 1 (CB1R) is mainly located in the CNS, while cannabinoid receptor 2 (CB2R) is located in the immune cells within the body. CB2R regulates inflammatory processes and fibroblast function.Purpose: We investigated the impact of CB2R agonist, JWH 133 and the antagonist, AM630 on lung tissue, applied directly before nicotine application.Material and methods: 40 mice were placed into 4 groups. The experimental groups received nicotine intraperitoneally at a dose of 0.05 mg/kg of body weight (BW) for 14 days. Group B also received AM630 (0.5mg/kg of BW), while Group A was administered with JWH133 (1 mg/kg of BW). Group N received nicotine alone. The Control group C received 0.9% NaCl. After decapitation, lung tissues were stained with H&E, Trichrome Masson's method, and IHC against CTGF and α-SMA. The digital image processing system Image J with the IHC profiler plugins was then employed, optical density and IHC optical density score were calculated.Results: In the N group, an increase in the thickness of alveolar spaces (9.16 SD4.95µm vs. 4.77SD2.99µm in the C group), leukocytes infiltration and collagen deposition has been observed(OD: 0.20 SD0.0vs 0.07SD0.04 in the C group). In the B group, the alveolar space thickness has been the highest (11.57SD8.13µm). Furthermore, in this group, hyperaemia, destruction of lung structure, hyperplasia of II type pneumocyte and interstitial fibrosis has been observed (OD: 0.23 SD0.08). In contrast, the lung tissue of the A group has had normal structure and the thinnest alveolar septum (3.88 SD2.64µm). The expression of CTGF and α-SMA has been the highest in the B group.Conclusion : Nicotine induces interstitial lung fibrosis that is enhanced by the CB2R antagonist and diminished by the CB2R agonist. Therefore, the CB2R agonist may offer a protection against fibrosis.